Lift The Flap Book INDORIA Assisted by Edugames to Improve Fourth-Grade Learning Outcomes - Iskandar, Salma Labibah; Fathurrahman, Moh. (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
In learning Pancasila Education at the elementary school, there are still obstacles, especially related to the material of indonesia's social cultural diversity. The lack of learning media updates and low motivation are obstacles for students in exploring cultural diversity in Indonesia which results in low achievement of student learning outcomes. The purpose of this study was to develop, test the effectiveness, and assess the feasibility of Lift The Flap Book INDORIA media assisted by Edugames to improve student learning outcomes in Pancasila Education, especially on cultural diversity material for grade IV Elementary School. This research uses the Research and Development (R&D) method with the ADDIE approach. The research subjects included material and media experts, a fourth grade teacher, and a farge group test of 22 fourth grade students of MI Gisikdrono Semarang and a sample of 7 students with purposive sampling technique. Data collection techniques include performance tests, observation, interviews, questionnaires and documentation. Data analysis was done descriptively qualitative, quantitative, and inferential statistics. The develooment of INDORIA's Lift The Flap Book is designed to provide knowledge while stimulating children's motor responses through visual and interactive activities. Based on the results of the feasibility analysis, this media is considered